Reversible image watermarking technique using LCWT and DGT - Fernandes.J, Bennilo; S, Sivakannan; N, Prabakaran; Thirugnanam, G. (International Journal of Engineering and Technology, 2017)
In this contemporary world procuring our confidential data against some unknown person is very significant. Thus to have a high reliability of data security watermarking technique is applied before transmitting the data. This proposed work LCWT and DGT decomposition gives an effective technique to protect hypertensive related information based on reversible watermarking. LCWT has the superiority of multi-resolution fundamental analysis of wavelet transform and reflects representation of image domain in LCT. And using DGT decomposition the patient information has to embed inside high frequency subband wavelet and the watermarked information will be extracted by the receiver without any loss, to reconstruct the original image information. The reliability of the proposed method is analyzed by comparing the experimental results of similarity index, normalization and peak signal to noise ratio.